1997
DOI: 10.1677/joe.0.1550055
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of glucose homeostasis and hepatic insulin resistance in ob/ob mice given oral molybdate

Abstract: Molybdate (Mo) exerts insulinomimetic effects in vitro. In this study, we evaluated whether Mo can improve glucose homeostasis in genetically obese, insulin-resistant ob/ob mice. Oral administration of Mo (174 mg/kg molybdenum element) for 7 weeks did not affect body weight, but decreased the hyperglycaemia (approximately 20 mM) of obese mice to the levels of lean (L) (+/+) mice, and reduced the hyperinsulinaemia to one-sixth of pretreatment levels. Tolerance to oral glucose was improved: total glucose area wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 40 publications
1
24
0
1
Order By: Relevance
“…In the present study, we observed that leptin treatment of ob/ob and STZ-treated ob/ob mice causes marked elevation of hepatic 11␤-HSD1 expression, reduction of body weight and circulating corticosterone levels, and reversal of hyperglycemia within 2 weeks without the use of insulin. Moreover, we also observed that leptin treatment of ob/ob mice increased insulin sensitivity and reduced the expression of PEPCK, a gluconeogenic enzyme that is correlated with the acceleration of gluconeogenic pathways in the ob/ob mouse liver (48). These results provide new evidence that leptin plays insulin-independent roles in the control of glucose metabolism and that modulation of hepatic 11␤-HSD1 expression may be involved in the glucose-lowering effects of leptin in obese mice.…”
Section: Discussionsupporting
confidence: 61%
“…In the present study, we observed that leptin treatment of ob/ob and STZ-treated ob/ob mice causes marked elevation of hepatic 11␤-HSD1 expression, reduction of body weight and circulating corticosterone levels, and reversal of hyperglycemia within 2 weeks without the use of insulin. Moreover, we also observed that leptin treatment of ob/ob mice increased insulin sensitivity and reduced the expression of PEPCK, a gluconeogenic enzyme that is correlated with the acceleration of gluconeogenic pathways in the ob/ob mouse liver (48). These results provide new evidence that leptin plays insulin-independent roles in the control of glucose metabolism and that modulation of hepatic 11␤-HSD1 expression may be involved in the glucose-lowering effects of leptin in obese mice.…”
Section: Discussionsupporting
confidence: 61%
“…Female ob/ob mice have been used extensively in metabolic studies concerning hepatic (and muscle) insulin sensitivity (8,42). To be able to compare our data with published work, we chose to use female ob/ob mice for the current experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of hepatic lipoprotein production to the development of hyperlipidemia in these mice is not clear. Hyperglycemia together with an increased glycolytic activity in ob/ob mice may lead to an increased availability of acetyl-CoA residues for DNL (7), as supported by increased hepatic expression levels and activities of glycolytic enzymes, i.e., glucokinase (8,9), phosphofructokinase (7), and pyruvate kinase (7,8). Furthermore, elevated plasma free fatty acid (FFA) levels (9) and increased hepatic expression of fatty acid translocase (FAT or CD36) and plasma membranefatty acid binding protein have been reported in this model (10).…”
mentioning
confidence: 99%
“…Blood glucose was measured using a glucometer (Elite, Bayer, Brussels, Belgium). Plasma insulin, corticosterone, total cholesterol, and triglyceride levels were determined as described (5,44). Protein concentrations in tissue homogenates were measured by the Bradford method.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%